Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1161/circulationaha.113.006797
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Chloride Intracellular Channel 4 Expression Contributes to Endothelial Dysfunction in Pulmonary Arterial Hypertension

Abstract: Background Chloride intracellular channel 4 (CLIC4) is highly expressed in the endothelium of remodelled pulmonary vessels and plexiform lesions of patients with pulmonary arterial hypertension (PAH). CLIC4 regulates vasculogenesis through endothelial tube formation. Aberrant CLIC4 expression may contribute to the vascular pathology of PAH. Methods and Results CLIC4 protein expression was increased in plasma and blood-derived endothelial cells from patients with idiopathic PAH (IPAH) and in the pulmonary vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 41 publications
(63 reference statements)
6
82
0
Order By: Relevance
“…25 Interestingly, activation of TLR4 by NETs was accompanied by increased expression of CLIC4 in HPAECs, consistent with the proinflammatory and proangiogenic phenotype ( Figure 5F). …”
Section: Toll-like Receptor 4 Mediates the Proinflammatory And Proangsupporting
confidence: 62%
See 1 more Smart Citation
“…25 Interestingly, activation of TLR4 by NETs was accompanied by increased expression of CLIC4 in HPAECs, consistent with the proinflammatory and proangiogenic phenotype ( Figure 5F). …”
Section: Toll-like Receptor 4 Mediates the Proinflammatory And Proangsupporting
confidence: 62%
“…The link between CLIC4 and TLR4 signaling will require further studies, but CLIC4 was shown to increase phosphorylation of p65 subunit of NFκB, important for the NFκB-induced hypoxia-inducible factor activation and pulmonary endothelial angiogenesis in vitro. 25 Having demonstrated that NETs increase pulmonary endothelial cell motility and angiogenic responses in vitro, we then investigated the angiogenic effects of NETs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This function of CLIC1 is resembled by a close relative, CLIC4, which mediates acidification of vacuoles in endothelial cells (34). However, it is important to note that CLIC4 has a number of additional functions, which do not seem to depend on anion currents, including the stabilization of phospho-smad2/3 as well as the p65 subunit of NFκB (35, 36). The interaction of CLIC4 with NFκB in endothelial cells is significant for pulmonary hypertension as it leads to activation of HIF1α and induction of an overall mesenchymal phenotype with invadopodia and stress fibers (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that CLIC4 has a number of additional functions, which do not seem to depend on anion currents, including the stabilization of phospho-smad2/3 as well as the p65 subunit of NFκB (35, 36). The interaction of CLIC4 with NFκB in endothelial cells is significant for pulmonary hypertension as it leads to activation of HIF1α and induction of an overall mesenchymal phenotype with invadopodia and stress fibers (36). Another CLIC family member, CLIC3, in turn contributes to cell invasion through recycling of MT1-MMP and integrin α5β1 to the cell surface suggesting that stabilizing proteins involved in cell-extracellular matrix interactions is a common theme of CLIC family members (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…PULMONARY ARTERIAL HYPERTENSION (PAH) is a cardiopulmonary disease with a poor prognosis that is characterized by elevated pulmonary arterial pressure and leads to progressive right heart failure and ultimately death (57). Pharmacological agents moderately improve the patients' symptoms and the hemodynamic parameters of severe PAH, but none significantly reduces mortality (4,42).…”
mentioning
confidence: 99%